Twenty-First Century Teaching Skills of Teachers in Chinese Educational Institutions in Central Philippines - Yusay, Regine; Bual, Joel; Madrigal, Dennis (Technium Social Sciences Journal, 2024)
Twenty-first teaching skills are necessary to meet the demands of the 21st-century educational curriculum. Anchored on the framework of 21st century learning and partnership for 21st century skills, this study assessed the teachers’ practice of 21st century teaching skills among Chinese schools in Central Philippines in terms of critical thinking, collaboration, communication, creativity and innovation, self-direction, making global connections, making local connections, and using technology as a tool for learning relative to their age, sex, educational attainment, years of teaching, and designation. Likewise, it compared their teaching skills assessment when grouped to demographics. Using the quantitative design, the 112 stratified randomly sampled teachers responded to the standardized questionnaire. It was responded using very great to very poor extent. The data were analyzed using mean, standard deviation, and independent sample t-test. Meanwhile, the researcher adhered to the Philippine Health Research Ethics Board (PHREB). Generally, their teaching skills extent was great. Also, there was no difference in their age, sex, educational attainment, and years of teaching. However, there was a difference in designation where high school rated higher than elementary teachers. Hence, trainings are essential in continuously improving in 21st century teaching skills. Also, the results partially validated the theory. With these, further studies are recommended to validate the claims.